Ionophore-mediated coupling between ion fluxes and amino acid absorption in mouse ascites-tumour cells. Restoration of the physiological gradients of methionine by valinomycin in the absence of adenosine triphosphate - Reid, M. (1974)
1. Preparations of mouse ascites-tumour cells depleted of ATP and Na(+) ions accumulated l-methionine, in the presence of cyanide and deoxyglucose, from a 1mm solution containing 80mequiv. of Na(+)/l and about 5mequiv. of K(+)/l. Valinomycin increased, from about 4 to 16, the maximum value of the ratio of the cellular to extracellular concentrations of methionine formed under these conditions without markedly affecting the distributions of Na(+) and of K(+). Similar observations were made with 2-aminoisobutyrate, glycine and l-leucine. Increasing the extracellular concentration of K(+) progressively decreased the accumulation of methionine in the presence of valinomycin. Over the physiological range of ionic gradients, the system behaved as though the absorption of methionine with Na(+) was closely coupled to the electrogenic efflux of K(+) through the ionophore. The process was insensitive to ouabain and so the sodium pump was probably not involved. 2. The amount of methionine accumulated during energy metabolism was similar to the optimal accumulation in the presence of valinomycin when ATP was lacking. It was also similarly affected by increasing the methionine concentration. 3. A mixture of nigericin and tetrachlorosalicylanilide mimicked the action of valinomycin. The anilide derivative inhibited the absorption of 2-aminoisobutyrate in the presence of valinomycin, but not in its absence. 4. Gramicidin inhibited methionine absorption and caused the preparations to absorb Na(+) and lose K(+). 5. The observations appear to verify the principle underlying the gradient hypothesis by showing that the tumour cells can efficiently couple the electrochemical gradient of Na(+) to the amino acid gradient.